Pewarna Alami Kunyit Dan Buah Naga Untuk Pengaplikasian Teknik Sablon - Mesah Nur Sejati; Ali Ramadhan; Tunjung Atmadi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Background: The spices turmeric and dragon fruit are daily human needs. Natural dyes have beautiful and distinctive colors that are difficult to imitate with synthetic dyes. Natural dyes can be used as a basis for screen printing techniques. Screen printing is a printing technique using a template. Purpose: mixing natural dyes turmeric and dragon fruit to apply screen printing techniques. Research method: experimental research. In this research, the natural dyes of turmeric and dragon fruit were mixed to apply the screen printing technique. Firstly, by collecting natural materials and reinforcing rubber. Next, make the dough until a strong dough is produced. After obtaining the water content in the dough. Next, screen printing is carried out onto fabric media. Findings: After mixing the natural dyes turmeric and dragon fruit to apply the screen printing technique, it shows that the color strength is very significant on the fabric media. Implication: mixing the natural dyes turmeric and dragon fruit for the application of screen printing techniques is very important to study and use as material. For future researchers, the theme we have taken here is that the originality is very strong, especially in the part about mixing the natural dyes turmeric and dragon fruit for the application of screen printing techniques. Become an evidence base in scientific development, especially in product design courses.